Монгол улсыг нэгтгэж, түүний тусгаар тогтнолыг сэргээхийн төлөө Лигдэн хутагт хаан, Цогт хунтайж нарын тэмцэл - Энхээ, Ц. (Historia Mongolarum, 2003)
Монголын эх түүхийн судалгаанд олонтаа нэр тэмдэглэддэг Лигдэн хаан, Цогт хунтайж нарын үйл ажилгааны тухайд холбогдох зарим асуудал тун бүдэг бөгөөд маргаантай байдаг билээ. Иймд энэ талаар өөрийнхөө бодол эргэцүүллийг хураангуй өгүүлэн, түүхч судлаачтай санал солилцох зорилгоор энэхүү өгүүллийг бичлээ. The first great of the Great Mongolian State was Chinggis Khan, who belonged to a Khiad Borgigon clan and the last great khaan of the State was Ligden Khan, who was the heir of Chinggis Khan. Ligden khan was chosen as great khan in 1604, when he was only 13, and rule up to 1634. In the time of fragmentation, he determined to unite Mongolian nation. Also he was elevated to Khuvilgan (Saint) rank. Ligden khaan was one of the strongest fighters against Manchu, for preserving the independence and unity of the Mongolian State. His political views, will, and desires for Khalkha were expressed in Khalkha Tsogt khaan epic. Either his struggle was defeated, it had valuable effect in the history of Mongolian nation.